2018
DOI: 10.1590/1982-02752018000100008
|View full text |Cite
|
Sign up to set email alerts
|

Coping materno da Síndrome de Down: identificando estressores e estratégias de enfrentamento

Abstract: Resumo O nascimento de uma criança com Síndrome de Down pode representar risco de estresse em mães, demandando estratégias de enfrentamento. Este estudo identificou os principais estressores e as estratégias de enfrentamento adotadas por nove mães de crianças com essa patologia. As participantes responderam a um roteiro de entrevista adaptado da Motivational Theory of Coping Scale – 12. Os principais estressores identificados foram: preconceito social, rotina de atendimentos, problemas de comportamento da cria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
2
0
3
Order By: Relevance
“…Research that aimed to analyze the hope in mothers of children with DS and its association with coping behaviors adopted by the family and the quality of the relationship of these mothers with the parents indicated that belief in God or religiosity were significantly associated with greater hope and quality in the relationship among parents of children with DS (14) . Similar results are presented in research that shows that, faced with difficulties, families of children with DS resort to religious faith and become more involved with the care of their child (4) , seeking assistance from professionals and meeting with the pedagogical team of school to outline strategies that can solve or minimally allow to deal actively with the problem, increasing the sense of competence and indicating an active coping with the stressor (21) .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Research that aimed to analyze the hope in mothers of children with DS and its association with coping behaviors adopted by the family and the quality of the relationship of these mothers with the parents indicated that belief in God or religiosity were significantly associated with greater hope and quality in the relationship among parents of children with DS (14) . Similar results are presented in research that shows that, faced with difficulties, families of children with DS resort to religious faith and become more involved with the care of their child (4) , seeking assistance from professionals and meeting with the pedagogical team of school to outline strategies that can solve or minimally allow to deal actively with the problem, increasing the sense of competence and indicating an active coping with the stressor (21) .…”
Section: Discussionsupporting
confidence: 70%
“…Studies devoted to understanding DS repercussions on siblings of children with DS have shown that they go through processes of acceptance, confusion, and various other complexities with which the syndrome is linked; yet, affective relationships and interaction competence between them are identified (21,22) . Support groups for siblings may help families to cope positively with challenges in situations involving the adaptation of siblings of children with DS (23) .…”
Section: Discussionmentioning
confidence: 99%
“…We chose this period because most families of children with DS consider it to be a critical event, with implications for their acceptance, adaptation, and willingness to follow recommendations for care. 7 Investigations in the Brazilian and international context have indicated that at the time of diagnosis, families usually experience negative feelings, such as tension, anxiety, stress, denial, punishment, 8 disorientation, loss of the idealized child during gestation, anxiety, [9][10] shock, 8,10,11 fear, sadness, anger, and frustration, 8,12 concern with society's response in the future. 15 A few families mentioned positive feelings.…”
Section: Introductionmentioning
confidence: 99%
“…O diagnóstico de deficiência ainda traz responsabilidades e exigências adicionais para os genitores que, além do cuidado, devem lidar com os tratamentos impostos pelo quadro clínico do bebê e com as expectativas sociais em relação a ele (Cunha, Blascovi-Assis, & Fiamenghi Jr., 2010;Scorgie, 2015), produzindo reverberações no próprio psiquismo dos pais (Reis & Paula, 2018). Nesse sentido, estudos que investigaram diferentes deficiências na faixa etária de 0 a 3 anos têm apontado para a importância de considerar a saúde mental dos responsáveis pelo bebê, cujas experiências são permeadas por altos níveis de cansaço, ansiedade e estresse (Chan et al, 2015;Goff et al, 2016;Razera, Trettene, Tabaquim, & Niquerito, 2017;Reis & Paula, 2018). Estudo realizado por Razera et al (2017), com mães de crianças com fissura labiopalatina, destacou o isolamento dos cuidadores em períodos de internação hospitalar, devido, em parte, à responsabilidade durante a recuperação da criança, ocasionando níveis elevados de estresse, fadiga e sobrecarga.…”
Section: Introductionunclassified
“…jul./set., 40(110), 2045PsicolArgum. -2070 dependência por cuidados e a rotina intensa de tratamentos (Couto et al, 2007;Oliveira-Menegotto & Lopes, 2009;Razera et al, 2017;Reis & Paula, 2018). Por isso, neste estudo entende-se como exigências emocionais as demandas psíquicas, bem como aquelas advindas do desgaste físico, que podem estar presentes no atendimento às necessidades do bebê e, consequentemente, no seu cuidado durante os primeiros meses de vida (ex.…”
Section: Introductionunclassified